THE INFLUENCE OF WORK ENVIRONMENT AND WORK STRESS ON EMPLOYEE PERFORMANCE IN THE GENERAL SECTION (RECTORATE) AT UPN VETERANS, EAST JAVA - Muhkhamad Edris; Rifki Suwaji (SEAN Institute, 2023)
PN Veteran East Java is one of the Indonesian state universities located in Surabaya, East Java. In 2014, UPN